2018
DOI: 10.1590/1678-4324-2016160246
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced Changes in the Electrophoretic Profile of Serum Albumin

Abstract: Albumin protein profiles were investigated in electrophoresis system in relation to the whole body exposition to the radiation. Two groups of rats Wistar were set up as the control (CG) and the irradiated one (IG

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…The changes in the body weights observed among the groups exposed to radiation show the potential of bodyweight reduction by exposure to gamma radiation (Table 1). Several studies have shown that oxidative stress can reduce total proteins especially when it interferes with the production of albumin which constitutes more than 60% of the total proteins (1,(28)(29)(30). The extracts of T. occidentalis and C. mannii show their potency in the prevention of weight loss and reduced total proteins due to gamma irradiation (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…The changes in the body weights observed among the groups exposed to radiation show the potential of bodyweight reduction by exposure to gamma radiation (Table 1). Several studies have shown that oxidative stress can reduce total proteins especially when it interferes with the production of albumin which constitutes more than 60% of the total proteins (1,(28)(29)(30). The extracts of T. occidentalis and C. mannii show their potency in the prevention of weight loss and reduced total proteins due to gamma irradiation (Table 2).…”
Section: Discussionmentioning
confidence: 99%